DEPDC1 facilitated malignant phenotypes and disease progression of liposarcoma by modulating KIF20A - Yu, Mingwei; Zhao, Huishan; Sun, Yujie (Frontiers in Endocrinology, 2025)
IntroductionDEP domain containing 1 (DEPDC1) has been well-known as a significant contributor to tumorigenesis and cancer progression. However, its potential oncogenic mechanism in liposarcoma is still unclear.MethodsIn this study, the expression and clinical relevance of DEPDC1 in sarcoma was assessed by employing data from The Cancer Genome Atlas (TCGA) data and conducting Kaplan-Meier online analyses, respectively. Furthermore, the impact of DEPDC1 on cellular functions of liposarcoma cell lines and its underlying mechanisms were studied using the in vitro assays.ResultsHere, our findings revealed that the expression levels of DEPDC1 and KIF20A were elevated in liposarcoma compared to the paired adjacent adipose tissues, with their expression positively correlating with the malignancy of liposarcoma. Moreover, patients with high DEPDC1 or KIF20A mRNA levels experienced shorter survival times. In vitro assays showed that DEPDC1 overexpression enhanced cell proliferation, migration, and invasion in 93T449 cells, whilst an opposite effect was observed in SW872 cells with DEPDC1 knockdown. Furthermore, potential interacting proteins of DEPDC1 were predicted by STRING, and the DEPDC1-KIF20A interaction was confirmed by co-immunoprecipitation in liposarcoma cells. The deletion of KIF20A partially mitigated the promoting effect of DEPDC1 on the malignant phenotype of liposarcoma cells and the activation of PI3K/AKT/mTOR signaling pathway.ConclusionsIn conclusion, this study suggested that DEPDC1 might interact with KIF20A to promote the occurrence and progression of liposarcoma by activating PI3K/AKT/mTOR signaling pathway.